Pengembangan Lembar Kerja Peserta Didik (LKPD) Bermuatan Kearifan Lokal Suku Sasak pada Mata Pelajaran Pendidikan Pancasila di Kelas IV SDN 1 Korleko Selatan - Iin Juliana; Khairun Nisa; Muhammad Erfan (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
This study aims to develop teaching materials in the form of student worksheets containing local wisdom of the Sasak tribe and to test their validity, practicality, and effectiveness in improving student learning outcomes. This research is a development research with the ASSURE model consisting of 6 stages, namely, 1) analyzing students, 2) formulating learning objectives, 3) selecting methods, media, and teaching materials, 4) utilizing media, technology, and teaching materials, 5) involving student participation, 6) evaluation and revision. The research subjects were 15 fourth-grade elementary school students with the object in the form of teaching materials "Student Worksheets". Data collection was carried out through validation sheets of material, media, and instrument experts, teacher and student response questionnaires, and multiple-choice tests (pre-test and post-test) of 20 questions. Validity analysis used Aiken's V and reliability used the KR-20 formula. The results showed a validity of 0.938 for the material, 0.875 for the media, and 0.975 for the test instrument. The reliability of the 20 multiple-choice questions was 0.71383, categorized as high. The worksheets were classified as very practical, based on 84% of student responses and 96% of teacher responses. They were also effective in improving learning outcomes from 37.33% to 79.66%, with an N-Gain of 0.67, categorized as moderate.